Alleviating ashermans: a success story - Das, Esha; Agrawal, Sarita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Asherman syndrome (AS) is characterised by formation of intrauterine synechia due to the destruction of basal layer of endometrium. It presents as oligomenorrhea, amenorrhoea and infertility. Treating Ashermans is a challenge. Patient XYZ, 28 years, presented with complaints of amenorrhea for 11/2 years. She was diagnosed with Ashermans Syndrome outside but the treatment did not work. We first gave cyclical hormones followed by hysteroscopic adhesiolysis. She conceived immediately after return of menses and delivered a term baby. Currently she has regular menstruation. Conclusion: Building up the endometrium on hormonal support pre- and post-surgery and instant conception on return of menstruation was the factor leading to successful management.